GERAKAN LITERASI SISWA DALAM PENINGKATAN MODEL PEMBELAJARAN PAKEM DI SDN PONDOK KELAPA 05 PAGI - Manurung, Alberth Supriyanto; Halim, Abdul (Universitas Esa Unggul, 2020)
Mathematics is the science of logic regarding form, arrangement, quantity, and concepts related to one another. In the concept is always related to everyday human life. Learning Mathematics in the form of the Literacy Movement students are not just increasing curiosity but always developing according to the times, Mathematics is the science of counting which aims to instill and develop the counting process in teachers. Based on observations at SDN Pondok Kelapa 05 Morning in the learning process, The teacher still uses conventional teaching methods or is centered on the teacher as an information provider, with the existence of the student literacy movement is expected to improve the good quality of each concept of problem-solving in the form of application problems.Â Kata kunci : Learning, Literacy, Mathematics